ChemInform Abstract: A Solvent‐Free Protocol for the Synthesis of 3‐Formyl‐2H‐chromenes via Domino Oxa Michael/Aldol Reaction. Issue 33 (19th August 2014) - Lanari, Daniela; Rosati, Ornelio; Curini, Massimo
Abstract Substrates with electron‐withdrawing groups give the undesired hemiacetal (V) as major product.